A fable for our entangled world: Reading Gary Shteyngart’s "Our country friends" (2021) in assemblage terms - Bryla, Martyna (Studia Anglica Posnaniensia, 2025)
This article focuses on Gary Shteyngart’s 2021 novel, Our country friends, which follows a multicultural group of American friends spending the COVID-19 lockdown at the country estate of Sasha Senderovsky, a Russian-American writer and “landowner.” Inspired by assemblage thinking and Thomas Newlin’s ecological reading of Anton Chekhov’s Uncle Vanya (1897), this study reads Our country friends as a novel that foregrounds interhuman relations in an entangled world. By invoking Anton Chekhov’s fin-de-siècle play, the novel opens up space for a trans-temporal reflection on a universally human affliction—a sense of wasted time and regret for opportunities not taken. Simultaneously, Shteyngart’s work taps into the anxieties of the present moment: the COVID-19 pandemic, mapped as a complex biological and political assemblage, and Donald Trump’s dysfunctional politics exacerbating the resulting chaos. Like Chekhov in Uncle Vanya, Shteyngart favors a deep-time, globally conscious perspective over a nation-centric one. Shteyngart’s protagonists are not immune from the world beyond the country estate but are instead embedded in several interconnected ecosystems: their immediate environment and the broader sociopolitical ecosystem of America, which in turn forms part of the global totality. Accordingly, in being at once deeply universal and painfully contemporary, Shteyngart’s novel is, to paraphrase Salman Rushdie’s words, a fable for our entangled world, which promises to remain relevant even as the COVID-19 pandemic recedes from view.